2015
DOI: 10.3389/fnbeh.2015.00194
|View full text |Cite
|
Sign up to set email alerts
|

Pain perception in people with Down syndrome: a synthesis of clinical and experimental research

Abstract: People with an intellectual disability experience both acute and chronic pain with at least the same frequency as the general population. However, considerably less is known about the pain perception of people with Down syndrome. In this review paper, we evaluated the available clinical and experimental evidence. Some experimental studies of acute pain have indicated that pain threshold was higher than normal but only when using a reaction time method to measure pain sensitivity. However, when reaction time is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 65 publications
(75 reference statements)
0
21
0
Order By: Relevance
“…Joint pain or muscle aches and vomiting/nausea were less commonly reported in individuals with vs. without DS. There is little evidence that people with DS experience both acute and chronic pain with a lower frequency than the rest of the population [28] . However, there is some evidence that parental perception of pain is less discriminant for children with DS than for their siblings without DS [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Joint pain or muscle aches and vomiting/nausea were less commonly reported in individuals with vs. without DS. There is little evidence that people with DS experience both acute and chronic pain with a lower frequency than the rest of the population [28] . However, there is some evidence that parental perception of pain is less discriminant for children with DS than for their siblings without DS [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Our main findings pertaining to abnormally reduced variability in cortical thicknesses implicate the postcentral gyrus (specifically Brodmann's area 1 and 3b), the lateral orbitofrontal gyri, the orbital gyrus and the central sulcus. The postcentral region, which includes Brodmann's areas 1 and 3b, is the site of the somatosensory cortex, the main sensory area for the sense of touch; abnormalities therein may be linked with observed abnormalities in pain perception among those with DS (Hennequin et al, 2000; McGuire and Defrin, 2015) along with other sensory processing delays (Bruni et al, 2010; Fidler and Nadel, 2007). The lateral orbitofrontal region has been associated with the integration of prior information with current information (Nogueira et al, 2017), and so abnormalities thereof may be linked with intellectual disabilities in DS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of post-operative pain management of children with DS suggest either an increased or similar need of post-operative pain analgesia as compared to non-DS patients (Gakhal et al , 1998; Valkenburg et al , 2012; Van Driest et al , 2013). Recent studies quantitatively comparing pain thresholds in children with and without DS have demonstrated that children with DS experience pain at the same frequency as children without DS, with delays in acute pain expression and magnified pain response (McGuire & Defrin, 2015; Valkenburg et al , 2015). Given that research reports equivalent pain frequency in children with DS, our finding of decreased analgesia use among DS-ALL patients may signify important deficiencies in current clinical care of these patients.…”
Section: Discussionmentioning
confidence: 99%